Out-of-the-box: Pertinent information. (June 2015) - James, Roger
Elections are a time at which objective fact vies with opinion and emotion leading up to the decision to vote. In the UK, the recent general election results proved to be a major surprise – one in which the hard data of the opinion polls and the questions asked in the focus groups were at odds with the expressed behaviour of the electorate. Before the pundits 'regroup' and the political groups re-establish their claimed hegemony over our intentions there is much to learn. For information scientists it is to recognize that the 'dark arts' of political campaigning contain many valuable techniques for effective information delivery and many lessons where information is irrelevant.